Fungal succession in decomposing ash leaves colonized by the ash dieback pathogen Hymenoscyphus fraxineus or its harmless relative Hymenoscyphus albidus - Kosawang, Chatchai; Børja, Isabella; Herrero, Maria-Luz; Nagy, Nina E.; Nielsen, Lene R.; Solheim, Halvor; Timmermann, Volkmar; Hietala, Ari M. (Frontiers in Microbiology, 2023)
The ascomycete Hymenoscyphus fraxineus, originating from Asia, is currently threatening common ash (Fraxinus excelsior) in Europe, massive ascospore production from the saprotrophic phase being a key determinant of its invasiveness. To consider whether fungal diversity and succession in decomposing leaf litter are affected by this invader, we used ITS-1 metabarcoding to profile changes in fungal community composition during overwintering. The subjected ash leaf petioles, collected from a diseased forest and a healthy ash stand hosting the harmless ash endophyte Hymenoscyphus albidus, were incubated in the forest floor of the diseased stand between October 2017 and June 2018 and harvested at 2-3 -month intervals. Total fungal DNA level showed a 3-fold increase during overwintering as estimated by FungiQuant qPCR. Petioles from the healthy site showed pronounced changes during overwintering; ascomycetes of the class Dothideomycetes were predominant after leaf shed, but the basidiomycete genus Mycena (class Agaricomycetes) became predominant by April, whereas H. albidus showed low prevalence. Petioles from the diseased site showed little change during overwintering; H. fraxineus was predominant, while Mycena spp. showed increased read proportion by June. The low species richness and evenness in petioles from the diseased site in comparison to petioles from the healthy site were obviously related to tremendous infection pressure of H. fraxineus in diseased forests. Changes in leaf litter quality, owing to accumulation of host defense phenolics in the pathogen challenged leaves, and strong saprophytic competence of H. fraxineus are other factors that probably influence fungal succession. For additional comparison, we examined fungal community structure in petioles collected in the healthy stand in August 2013 and showing H. albidus ascomata. This species was similarly predominant in these petioles as H. fraxineus was in petioles from the diseased site, suggesting that both fungi have similar suppressive effects on fungal richness in petiole/rachis segments they have secured for completion of their life cycle. However, the ability of H. fraxineus to secure the entire leaf nerve system in diseased forests, in opposite to H. albidus, impacts the general diversity and successional trajectory of fungi in decomposing ash petioles.